Contested Identities: Power and the Fictions of Ethnicity, Ethnography and History in Rwanda - Jefremovas, Villia (Anthropologica, 2022)
This article examines the process through which different interpretations of ethnicity and statehood in Rwanda have been used to create and justify policies of exclusion, inclusion and claims to legitimacy, from the colonial period to the present day. Arguing that the roots of such politics can be found in the politics of the precolonial state, it considers how they have been transformed, not created, by colonial and postcolonial governments. Viewing the representation of ethnicity and statehood over time as fictions of ethnicity, ethnography and history, this article illustrates the process of creation and recreation of these fictions and their impact on Rwandan lives.